\(=\dfrac{7}{5}\cdot\dfrac{15}{49}-\left(\dfrac{4}{5}-\dfrac{2}{3}\right):\dfrac{11}{5}\)
\(=\dfrac{3}{7}-\dfrac{2}{15}\cdot\dfrac{5}{11}\)
\(=\dfrac{3}{7}-\dfrac{2}{33}=\dfrac{99-14}{33\cdot7}=\dfrac{85}{231}\)
\(=\dfrac{7}{5}\cdot\dfrac{15}{49}-\left(\dfrac{4}{5}-\dfrac{2}{3}\right):\dfrac{11}{5}\)
\(=\dfrac{3}{7}-\dfrac{2}{15}\cdot\dfrac{5}{11}\)
\(=\dfrac{3}{7}-\dfrac{2}{33}=\dfrac{99-14}{33\cdot7}=\dfrac{85}{231}\)
x : \(\dfrac{2}{3}\) = 150 \(\dfrac{35}{9}\) : x = \(\dfrac{35}{6}\)
\(\dfrac{49}{7}\) : x =\(\dfrac{49}{5}\)
1 - { 5\(\dfrac{4}{9}\) + x - 7\(\dfrac{7}{18}\) }: 15\(\dfrac{3}{4}\) = 0
1 CM
a, \(\left(\dfrac{1}{1}+\dfrac{1}{3}+\dfrac{1}{5}+...+\dfrac{1}{2n-1}\right)-\left(\dfrac{1}{2}+\dfrac{1}{4}+...+\dfrac{1}{2n}\right)=\dfrac{1}{n+1}+\dfrac{1}{n+2}+...+\dfrac{1}{2n}\)( n∈Z)
b, \(\dfrac{1}{26}+\dfrac{1}{27}+...+\dfrac{1}{50}=\dfrac{99}{50}-\dfrac{97}{49}+...+\dfrac{7}{4}-\dfrac{5}{3}+\dfrac{3}{2}\)
Tính nhanh :
\(C=\dfrac{1}{3}+\dfrac{-3}{4}+\dfrac{3}{5}+\dfrac{1}{57}+\dfrac{-1}{36}+\dfrac{1}{15}+\dfrac{-2}{9}\)
\(D=\dfrac{1}{2}+\dfrac{-1}{5}+\dfrac{-5}{7}+\dfrac{1}{6}+\dfrac{-3}{35}+\dfrac{1}{3}+\dfrac{1}{41}\)
\(E=\dfrac{-1}{2}+\dfrac{3}{5}+\dfrac{-1}{9}+\dfrac{1}{127}+\dfrac{-7}{18}+\dfrac{4}{35}+\dfrac{2}{7}\)
Chứng minh rằng P>3 biet P= \(\dfrac{5}{2×1}+\dfrac{4}{1×11}+\dfrac{3}{11×2}+\dfrac{1}{2×15}+\dfrac{13}{15×4}+\dfrac{15}{4×43}+\dfrac{13}{43×8}\)
\(B=\left(\dfrac{0,4-\dfrac{2}{9}+\dfrac{2}{11}}{1,4-\dfrac{7}{9}+\dfrac{7}{11}}-\dfrac{\dfrac{1}{3}-0,25+\dfrac{1}{5}}{1^1_6-0,875+0,7}\right).\dfrac{1842009}{1842010}\)
1, so sánh A;B biết: A=\(\left(\dfrac{\left(3\cdot\dfrac{2}{15}+\dfrac{1}{5}\right):2\cdot\dfrac{1}{2}}{\left(5\cdot\dfrac{3}{7}-2\cdot\dfrac{1}{4}\right):\dfrac{443}{56}}\right);B=\dfrac{1,2:\left(1\cdot\dfrac{1}{5}.1\cdot\dfrac{1}{4}\right)}{0,32+\dfrac{2}{25}}\)
Hãy chọn cặp gồm hai phân số bằng nhau.
\(\dfrac{15}{-10}\) và \(\dfrac{5}{4}\)
\(\dfrac{-3}{2}\) và \(\dfrac{2}{-3}\)
\(\dfrac{2}{-3}\) và \(\dfrac{-15}{-12}\)
\(\dfrac{15}{-10}\) và \(\dfrac{-3}{2}\)
Cho S = \(\dfrac{1}{2}+\dfrac{1}{3}+\dfrac{1}{4}+...+\dfrac{1}{48}+\dfrac{1}{49}+\dfrac{1}{50}\)và P = \(\dfrac{1}{49}+\dfrac{2}{48}+\dfrac{3}{47}+...+\dfrac{48}{2}+\dfrac{49}{1}\). Tính \(\dfrac{S}{P}\)
a) \(\dfrac{\left(3+\dfrac{1}{6}\right)-\dfrac{2}{5}}{\left(5-\dfrac{1}{6}\right)+\dfrac{7}{10}}\)
b) \(\dfrac{\left(4,08-\dfrac{2}{25}\right):\dfrac{4}{17}}{\left(6\dfrac{5}{9}-3\dfrac{1}{4}\right).2\dfrac{2}{7}}\)
c) \(\dfrac{2-\dfrac{1}{4}+\dfrac{1}{3}-\dfrac{3}{5}}{3-\dfrac{1}{5}-\dfrac{5}{3}}\)